Kebijakan Pengembangan Koleksi dan Pemanfaatannya di Perpustakaan Perguruan Tinggi (Analisis Penerapan Kebijakan Pengembangan Koleksi Perpustakaan Utama Universitas Islam Negeri Syarif Hidayatullah Jakarta) - Iswanto, Rahmat (Perpustakaan STAIN Curup, 2017)
The assumption is there are many academic libraries of Indonesia especially under Minister of Religion Affairs (MORA) which hardly meet a demand of their usersâ needs because their collection management or collection development policies do not prepare well. Actually to create a better collection, an academic library has to plan its collection well. This research has done with a purpose of inspecting a collection development policy of an academic library in Indonesia and its implementation. The collection development policy of main library of State Islamic University Syarif Hidayatullah at Jakarta in 2008 is the object of this research. This research has done by a descriptive qualitative approach that inspects deeply by means of any deep interview, observation, and document analysis. Having examined the formulation of its collection development policy we know the context of policyâs formulation, some actors who formulate, the roles of the head of the library, the attitude of the university and some values that influence. Having examined its implementation we know that the aims of the policy have achieved or not.